2022
DOI: 10.3390/ijerph192315814
|View full text |Cite
|
Sign up to set email alerts
|

Flourishing or Languishing? Predictors of Positive Mental Health in Medical Students during the COVID-19 Pandemic

Abstract: During the COVID-19 pandemic, medical students were burdened with high levels of stress, anxiety, and depression. The objective of the present study was to investigate predictors of positive mental health among medical students during the COVID-19 pandemic. We conducted an online survey from September 2021 to March 2022. We applied the snowball recruitment technique involving medical students from the University of Catania, Italy. We administered, anonymously, a questionnaire about demographic characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 56 publications
1
4
1
Order By: Relevance
“…The results showed that 42.6% of participants reported flourishing mental health, 36.2% reported moderate mental health and 21.2% had languishing mental health. These results are in contrast with those collected in Italy where it was found that 34.8% reported a languishing mental health, 53.4% moderate and 11.8% flourishing: this difference could be due to the fact that the Italian sample was surveyed during the COVID-19 pandemic (Concerto et al, 2022), probably worsening mental health in the general population. In turn, the percentage of flourishing mental health was slightly lower than that reported by other authors (Polhuis et al, 2022).…”
Section: Discussioncontrasting
confidence: 94%
“…The results showed that 42.6% of participants reported flourishing mental health, 36.2% reported moderate mental health and 21.2% had languishing mental health. These results are in contrast with those collected in Italy where it was found that 34.8% reported a languishing mental health, 53.4% moderate and 11.8% flourishing: this difference could be due to the fact that the Italian sample was surveyed during the COVID-19 pandemic (Concerto et al, 2022), probably worsening mental health in the general population. In turn, the percentage of flourishing mental health was slightly lower than that reported by other authors (Polhuis et al, 2022).…”
Section: Discussioncontrasting
confidence: 94%
“…Conversely, in our previous qualitative study on this population (Wammes et al, 2022), emerging adults with preexisting mood and anxiety disorders voiced both positive and negative reactions at the outset of the COVID-19 pandemic. Although these two studies were not longitudinal, the change in emotional valence in the same demographic supports existing observations in the literature that emerging adults with preexisting mental illness were at risk of deterioration in the pandemic (Concerto et al, 2022). It also supports the observation that these individuals represent a subgroup that deteriorated as the pandemic continued, unlike some other groups (often without mental illness or marginalization) which remained stable or improved (Paton et al, 2023).…”
Section: Discussionsupporting
confidence: 77%
“…While many emerging adults regained stability as the pandemic progressed into 2021, a sizable minority experienced ongoing deterioration (Paton et al 2023). Deterioration appeared to be more consistent in emerging adult cohorts who had a pre-existing heightened level of distress prior to the pandemic (Shanahan et al 2022), and in cohorts with preexisting mental illness (Thorpe & Gutman, 2022, Concerto et al, 2022, Paton et al, 2023.…”
mentioning
confidence: 97%
“…8 For instance, trait anxiety has been related to a higher risk of developing anxiety disorders or depression. 9,10 In the case of the COVID-19 pandemic, recent studies showed that the first lockdown was associated with a higher prevalence of anxiety 11 and a reduction in mood 12,13 at the population level. However, it is still unclear how the interaction among biological, psychological, and environmental factors may lead to mental illness.…”
mentioning
confidence: 99%
“…In line with this, Taylor and colleagues 23 demonstrated that worries about the dangerousness of the virus were the most important factor mediating the subjective stress associated with the current situation. Furthermore, Concerto and colleagues 13 observed that depressive temperament could worsen the effects of the COVID-19 pandemic on the mental health of young adults. However, the role of intolerance of uncertainty remains unclear as this personality trait did not strongly predict subjective fear of COVID-19 (it was only a trend level, or only in combination with anxiety sensitivity 21 ).…”
mentioning
confidence: 99%